DETERMINAN KINERJA LEMBAGA ZAKAT: PERAN PENCEGAHAN KECURANGAN SEBAGAI VARIABEL MEDIASI DENGAN PENDEKATAN AKUNTANSI FORENSIK SYARIAH - Mutiara Rizqi Nur Rachmi; Reskino (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
As a country with the first largest Muslim population in the world, it should be able to make zakat funds paid by muzakki to address the problem of poverty in Indonesia. However, the Muslim community is still reluctant to channel their zakat funds to official zakat institutions. They prefer to pay their zakat to ustadz or mosques whose financial reports are still informal. This is also due to zakat institutions that have not adopted good governance and institutional inconsistencies in providing services and poor management. the purpose of the influence of governance, internal control, and institutional culture affects fraud prevention, and fraud prevention can mediate the relationship between governance, internal control, and institutional culture on the performance of zakat institutions. the method in this research is qualitative by distributing questionnaires. The difference between this research is the addition of internal control variables and institutional culture which are expected to affect the performance of zakat institutions. The results of this study are that internal control affects fraud prevention, fraud prevention affects the performance of zakat institutions and fraud prevention can mediate the relationship between internal control and zakat institution performance. This is because the internal controls that have been carried out zakat institutions have carried out the process of selecting human resources efficiently and effectively. besides that, the institution has given appreciation to employees for their performance and has committed to integrity by implementing applicable policies and procedures to improve the performance of zakat institutions.